Taxonomy of intertidal cheilostome Bryozoa of Maceió, northeastern Brazil. Part 1: Suborders Inovicellina, Malacostegina and Thalamoporellina - Vieira, Leandro M.; Almeida, Ana C.s.; Winston, Judith E. (Zootaxa, 2016)
Thirteen cheilostome bryozoan species from intertidal habitats of Maceió, Alagoas State, Brazil, are reported here. We describe four new species: Aetea cultrata n. sp., Biflustra marcusi n. sp., Biflustra sphinx n. sp. and Jellyella brasiliensis n. sp. Two other species of Inovicellina, Aetea arcuata Winston & Hayward, 2012, and Aetea curta Jullien, 1888, and four species of Malacostegina, Arbocuspis bellula (Hincks, 1881), Arbocuspis bicornis (Hincks, 1881), Arbocuspis ramosa (Osburn, 1940), and Jellyella tuberculata (Bosc, 1802), are reported on drift algae. Three species of Thalamoporellina are found for the first time in Maceió, Labioporella tuberculata Winston, Vieira & Woollacoot, 2014, Steginoporella magnilabris (Busk, 1854) and Thalamoporella floridana Osburn, 1940.